1998
DOI: 10.1007/s004230050095
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Kupffer cell blockade to prevent disseminated intravascular coagulation in endotoxemic rats despite improved survival

Abstract: These results confirm reports on the protective potential of GdCl3 pretreatment in experimental endotoxemia. However, the present study does not support the concept of DIC as a strong prognostic criterion for the outcome of sepsis and septic shock. Furthermore, the results presented suggest a minor role for KC in LPS-mediated activation of coagulation and indicate an involvement of KC in LPS-associated lethality independent of the coagulation system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…It has previously been reported that gadolinium administration is not able to prevent the haemodynamic alterations of acute endotoxaemia (Fujii et al 1998). Similarly, despite improved survival, gadolinium chloride failed to prevent laboratory and clinical signs of disseminated intravascular coagulation in endotoxaemic rats (Ruttinger et al 1998).…”
Section: Discussionmentioning
confidence: 96%
“…It has previously been reported that gadolinium administration is not able to prevent the haemodynamic alterations of acute endotoxaemia (Fujii et al 1998). Similarly, despite improved survival, gadolinium chloride failed to prevent laboratory and clinical signs of disseminated intravascular coagulation in endotoxaemic rats (Ruttinger et al 1998).…”
Section: Discussionmentioning
confidence: 96%
“…Although activation of Kupffer cells has been significantly inhibited by GdCl 3 in models of both in vivo hepatic I/R and isolated perfused rat liver [21][22][23][24], there is evidence that administration of GdCl 3 results in a pronounced rise in serum cytokine activity, es-pecially TNF, and a slight rise in liver enzyme activity [22]. In contrast, there is strong evidence that administration of high-dose IVIG can suppress Kupffer cell activation and down-regulate proinflammatory cytokine expression.…”
Section: Discussionmentioning
confidence: 99%
“…Although activation of Kupffer cells has been significantly inhibited by gadolinium chloride (GdCl 3 ) (Aldrich Chemical, Milwaukee, WI, USA) in models of in vivo hepatic I/R and isolated‐perfused rat liver [15, 18, 19, 20,21, 22, 23], the mechanisms mediating this inhibition have not been totally elucidated. It has been demonstrated that application of GdCl 3 during hepatic I/R decreases the mortality rate [24], attenuates purine nucleoside phosphorylase [25], improves functional parameters of the liver [18, 26], reduces platelet accumulation in cold perfused rat liver, prevents apoptosis of sinusoidal endothelial cells [27], attenuates neutrophil infiltration, and decreases myeloperoxidase activity [28].…”
mentioning
confidence: 99%
“…A number of studies suggest that the inhibitory effect of gadolinium chloride (GdCl 3 ) against Kupffer cell (KCs) activation shows potential as a protective intervention in rat models of in vivo hepatic reperfusion injury and isolated perfused livers (13). It has also been shown that treatment of liver ischemia-reperfusion injury with GdCl 3 reduces the mortality rate, attenuates neutrophil infiltration and decreases myeloperoxidase activity, improves hepatic function, reduces platelet accumulation in cold perfused livers, and prevents apoptosis of sinusoidal endothelial cells (4).…”
Section: Introductionmentioning
confidence: 99%